Frequency and Risk Factors for RBC Alloimmunization in Patients Undergoing Surgery in Tehran, Iran: the Role in Improving Type and Screening Tests - Moradinasab, Susan; Gharehbaghian, Ahmad; Abdolahi, Alireza (Archives of Advances in Biosciences, 2019)
Introduction: Alloimmunization to red blood cell antigens is one of the main complications of transfusion therapy. The appropriate pre-transfusion tests are necessary in order to minimize hemolytic reactions related to RBC alloantibodies. The aim of this study was to determine the frequency and specificity of RBC alloantibodies detected during pre-transfusion tests in addition to risk factors of alloimmunization in the hospitalized population in Tehran, Iran. Materials and Methods: In this retrospective study, the characteristics and type of alloantibodies in 31 alloimminized patients among 6029 hospitalized patients of Imam Khomeini general hospital were examined during September 2016 to January 2017. Results: The RBC alloantibody prevalence was 0.5% with the male: female ratio of 1:5.2. The most frequent antibodies were anti-D (30%), anti-E (24%) and anti-K (12%). Female sex, age, history of transfusion and pregnancy or abortion history were associated with alloimmunization. Conclusion:The alloimmunization rate were relatively low in hospitalized patients in this study. Female sex, age, history of transfusion and pregnancy sound to be the risk factors of alloimmnization.